2011
DOI: 10.1073/pnas.1101210108
|View full text |Cite
|
Sign up to set email alerts
|

Predicting human blood viscosity in silico

Abstract: The viscosity of blood has long been used as an indicator in the understanding and treatment of disease, and the advent of modern viscometers allows its measurement with ever-improving clinical convenience. However, these advances have not been matched by theoretical developments that can yield a quantitative understanding of blood's microrheology and its possible connection to relevant biomolecules (e.g., fibrinogen). Using coarse-grained molecular dynamics and two different red blood cell models, we accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
246
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 304 publications
(255 citation statements)
references
References 39 publications
5
246
0
Order By: Relevance
“…Such a viscous environment around single cells is supposed to mimic the effective high-shearrate viscosity of the crowded conditions present in WB (17). Therefore, the shear-thinning paradigm is rooted in RBCs' ability to tank-tread whatever the Ht in response to high shear stresses (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a viscous environment around single cells is supposed to mimic the effective high-shearrate viscosity of the crowded conditions present in WB (17). Therefore, the shear-thinning paradigm is rooted in RBCs' ability to tank-tread whatever the Ht in response to high shear stresses (7).…”
mentioning
confidence: 99%
“…Macromolecules dispersed in the plasma, such as fibrinogen, induce an attractive force between RBCs, leading to their aggregation (5). Because RBCs have a biconcave disk-like shape at rest, they form long floppy rouleaux structures that can reversibly and continuously break down to single flowing discocytes for increasing shear rates up to tens of seconds −1 (6,7). This change in microstructure is indeed accompanied by a strong viscosity drop from ∼ 100 cP down to about ∼ 10 cP (3).…”
mentioning
confidence: 99%
“…Furthermore, numerical predictions of RBC deformations show significant discrepancies with experimental observations. Indeed, experiments report only the stationary stretched shape of cells steadily aligned in the flow at high shear rates, whereas recent numerical studies predict "breathing" dynamic states with strong shape deformations at low shear rates for both RBCs and elastic capsules (9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 98%
“…To date, there has been little experimental work on the connection between the mechanical properties of RBCs and their dynamics in shear flow (5-8), compared with the many numerical and theoretical recent studies reported for capsules (9)(10)(11) and red blood cells (12)(13)(14)(15)(16). Surprisingly, all investigations dealing with RBC orientation in flow focus on a very particular case in which the axis of symmetry of the cell lies in the shear plane.…”
mentioning
confidence: 99%
See 1 more Smart Citation